Popliteal Sciatic Block as a Safe Anesthetic Alternative for High-risk Below-knee Surgeries - Smita Ubhe; Shweta Khatri (Annals of African Medicine, 2026)
Abstract Background: Anesthetic management of high-risk patients undergoing emergency below-knee surgery is challenging because of comorbidities such as ischemic heart disease, poorly controlled diabetes mellitus, renal and hepatic dysfunction, and coagulation abnormalities. Neuraxial and general anesthesia may carry significant risks in these patients. Ultrasound-guided peripheral nerve blocks may provide effective anesthesia with minimal hemodynamic disturbance. Objectives: To assess the feasibility and efficacy of combined ultrasound-guided popliteal sciatic and femoral nerve blocks for surgical anesthesia and postoperative analgesia in high-risk patients undergoing urgent below-knee procedures. Materials and Methods: This case series included five high-risk patients with multiple comorbidities scheduled for urgent below-knee surgery. Comorbidities included ischemic heart disease, poorly controlled diabetes mellitus, renal and hepatic dysfunction, and abnormal coagulation profiles. Ultrasound-guided popliteal sciatic and femoral nerve blocks were performed using ropivacaine and lignocaine, with dexmedetomidine as an adjuvant. Intraoperative hemodynamic stability, adequacy of anesthesia, requirement for conversion to general anesthesia, postoperative analgesia, and block-related complications were assessed. Results: Combined nerve blocks provided satisfactory surgical anesthesia in all five patients. None required conversion to general anesthesia. Hemodynamic parameters remained stable throughout the perioperative period. Postoperative analgesia was effective and prolonged in all patients. No significant block-related complications were observed. Conclusion: Combined ultrasound-guided popliteal sciatic and femoral nerve blocks may provide a reliable anesthetic alternative for high-risk patients undergoing urgent below-knee surgery. They can provide satisfactory surgical anesthesia, effective postoperative analgesia, and perioperative hemodynamic stability when conventional neuraxial or general anesthesia may be associated with increased risk.